2020
DOI: 10.1039/d0tc01795g
|View full text |Cite
|
Sign up to set email alerts
|

Candle flame-treatment as an effective strategy to enhance the photoelectrochemical properties of Ti-doped hematite thin films

Abstract: This work reports a simple, low cost and highly reliable strategy to enhance the photoelectrochemical (PEC) properties of the liquid phase deposited Ti-doped hematite thin films by flame-treatment. The samples...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…In our previous study on the candle flame‐treatment of Ti‐doped hematite thin films, the presence of oxygen vacancies was demonstrated by using back and forth oxidizing and reducing flames. The obtained results showed that the photocurrent density decreased considerably upon using an oxidizing flame 44 …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In our previous study on the candle flame‐treatment of Ti‐doped hematite thin films, the presence of oxygen vacancies was demonstrated by using back and forth oxidizing and reducing flames. The obtained results showed that the photocurrent density decreased considerably upon using an oxidizing flame 44 …”
Section: Resultsmentioning
confidence: 93%
“…In our previous work, the details for the preparation of iron hexafluoride complex precursors were given. 44 A 40ml solution of 0.5 M boric acid, 10 ml of iron hexafluoride complex solution, and 15 ml deionized (DI) water were mixed to obtain the final treatment solution for the growth of hematite thin films. Zr-doping was performed by adding the appropriate amounts of 45 wt% hexafluorozirconic acid (H 2 ZrF 6 ) solution to the treatment solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations